Design of a photovoltaic fast-charging station for electric three wheelers vehicles in West Africa - Thiam Ababacar; Ndiaye Serigne Mourtalla; Ndiaye Mouhamadou Fadilou; Ka Ibrahima (E3S Web of Conferences)
Electric tricycles are one of the most promising options for reducing CO2 emissions in sub-Saharan Africa, with lower energy requirements. They are also suitable for transporting passengers and goods in rural areas of sub-Saharan Africa, where urbanization is rife. The lack of recharging infrastructure is holding back the development of tricycles. This paper proposes a methodology for the design of a photovoltaic (PV)-battery stand-alone fast charging station for electric tricycles in Thienaba, Senegal. An ultra-fast charging station powered by photovoltaic panels was designed, modelled and simulated using the Matlab/Simulink platform. The results of this work gave a photovoltaic array with a peak power equal to 45 kW. At least, eight tricycles can be charged between 11 am and 2 pm. At the same time, the storage system can be charged up to 70% of its total charge.